Integrating the Past and Locality: A Conceptual Framework for Disaster Mitigation of Mount Marapi Based on Historical and Community Knowledge - Muhajir, Ahmad (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2025)
Mount Marapi in West Sumatra is one of the most active volcanoes in Indonesia, with a long history of eruptions and lahar floods dating back to the colonial era. Despite various disaster mitigation approaches that have been developed, most remain technocratic and have yet to fully integrate historical knowledge sources and the local narratives of surrounding communities. This article proposes a conceptual framework for disaster mitigation grounded in historical and community-based perspectives, using Mount Marapi as a case study. The interdisciplinary approach combines disaster history, disaster anthropology, spatial geography, and public policy. The analysis draws on colonial archival reconstruction, synthesis of contemporary literature, and exploration of local knowledge held by the Nagari communities on the slopes of Mount Marapi. The findings show that colonial-era archives from the Dutch East Indies contain valuable data on lahar flow patterns, eruption intensity, and policy responses, which can inform historically risk-based mitigation systems. Meanwhile, local communities possess ecological and spiritual knowledge of natural signs preceding disasters, passed down through generations and forming socially rooted early warning systems. However, integrating these two knowledge systems into contemporary mitigation policy remains limited, primarily due to the lack of formal mechanisms to accommodate collective memory as a policy foundation. Through narrative and policy analysis, this article formulates a conceptual strategy that positions history as an active risk archive and communities as co-producers of mitigation strategies. It also proposes actionable steps such as digitizing disaster archives, creating a historical hazard atlas, and strengthening locally based early warning systems. Thus, disaster history serves as a retrospective memory and an operational foundation for developing contextual, participatory, and sustainable disaster mitigation systems.